1998
DOI: 10.1046/j.1432-1327.1998.2530328.x
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal helix of human apolipoprotein AII promotes the fusion of unilamellar liposomes and displaces apolipoprotein AI from high‐density lipoproteins

Abstract: To assess the functional properties of apolipoprotein (apo) AII and to investigate the mechanism leading to the displacement of apo AI from native and reconstituted high-density lipoproteins (HDL and r-HDL) by apo AII, wild-type and variant apo AII peptides were synthesized. The wild-type peptides, residues 53Ϫ70 and 58Ϫ70, correspond to the C-terminal helix of apo AII and are predicted to insert at a tilted angle into a lipid bilayer. We demonstrate that both the apo AII-(53Ϫ70) peptide, and to a lesser exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The oblique insertion into the lipid bilayer often causes membrane disruption by promoting highly curved hemifusion intermediates, leading to fusion. Tilted peptides have been discovered in viral fusion proteins as well as in many proteins involved in lipid/ lipoprotein metabolism, such as apoB-100 signal peptide ( 41 ), LPL and hepatic lipase ( 42 ), cholesteryl ester transfer protein ( 42 ), lecithin cholesterol acyltransferase ( 43 ), apoA-II ( 44 ), and MTP ( 45 ). In the case of apoC-III, the predicted oblique peptide has a tilted angle of 40° with the interface plane ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The oblique insertion into the lipid bilayer often causes membrane disruption by promoting highly curved hemifusion intermediates, leading to fusion. Tilted peptides have been discovered in viral fusion proteins as well as in many proteins involved in lipid/ lipoprotein metabolism, such as apoB-100 signal peptide ( 41 ), LPL and hepatic lipase ( 42 ), cholesteryl ester transfer protein ( 42 ), lecithin cholesterol acyltransferase ( 43 ), apoA-II ( 44 ), and MTP ( 45 ). In the case of apoC-III, the predicted oblique peptide has a tilted angle of 40° with the interface plane ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The interesting hypothesis in the story of tilted peptides is that tilt might have functional consequences. Tilt was first postulated and further demonstrated to be related to the fusogenic ability of fusion proteins of viruses (13,38), to the secretion yield of secreted proteins (13,15), and to the catalytic activity of some enzymes involved in lipid metabolism (17,35). The reason for this effect was suggested to be in the ability of such fragments to adsorb on and penetrate into the hydrophobic interfaces, and to destabilize the packing of acyl chains.…”
Section: Discussionmentioning
confidence: 99%
“…Tilted peptides have been identified in many proteins and protein fragments interacting with lipids such as viral fusion proteins (14), signal peptides of membrane-translocated proteins (15), and proteins involved in lipid metabolism (16). In the latter, they may increase the accessibility of enzymes to hydrophobic substrates (12,17,18). Hence, in contrast with classical amphipathic helices currently found in proteins and supported to promote protein stability, tilted peptides are a signature for instability (13).…”
mentioning
confidence: 99%
“…Small peptides can adopt ␣ and ␤ type structures (12,22,33). It was shown that the ability of the Ebola virus peptide to induce lipid destabilization correlates with an ␣-helical structure, in the absence of Ca 2ϩ (33).…”
mentioning
confidence: 99%
“…This method is based on an analysis of the shape and position of hydrophobic clusters in a given protein sequence (13). The 25 to 35 fragment (AIGLAWIPYFG) shows a hydrophobicity profile similar to that of the SIV tilted peptide, well known for its fusogenic properties (22,26), although, as shown on Fig. 1, the two stretches have no sequence identity.…”
mentioning
confidence: 99%